Cryoconservation of koovalam (Aegle marmelos L.Corr.) by encapsulation-dehydration technique - Deepa E (Department of Plant Biotechnology, College of Agriculture, 2018)
The study entitled “Cryoconservation of Koovalam (Aegle marmelos L. Corr.) by encapsulation-dehydration technique,” was carried out in the Department of Plant Biotechnology, College of Agriculture, Vellayani during 2015-2017. The objectives of the present study were to standardize a cryopreservation protocol for Aegle marmelos using encapsulation and dehydration technique and to assess the genetic fidelity of plantlets regenerated from encapsulated axillary buds after cryostorage, using molecular markers.